HIGIENE DAN SANITASI MAKANAN KAITAN DENGAN KEBERADAAN BAKTERI ESCHERICHIA COLI PADA WARUNG NASI DI PASAR CIKURUBUK KOTA TASIKMALAYA - Halimatussadiyah, Halimatussadiyah; Novianti, Siti; Maywati, Sri (Fakultas Ilmu Kesehatan Universitas Siliwangi, 2024)
Markets are one of the public places (TTU) that have a risk of being a place for contamination of disease transmission through media, one of which is food. Food stalls are also one of the places that provide food which gets quite a lot of visits from consumers, especially visitors to traditional markets to get or enjoy the various kinds of food they want. The results of a preliminary study conducted by researchers were observations of the Cikurubuk market in Tasikmalaya City, where there were 32 rice stalls, which sold mixed rice dishes with various different side dishes. It can be seen from the preliminary study that rice stalls still do not pay attention to good food processing practices and sanitation hygiene with the presence of Escherichia coli bacteria in food at the Cikurubuk Market, Tasikmalaya City. The aim of this research is to determine and analyze the relationship between food hygiene and sanitation and the presence of Escherichia coli bacteria. The research method used was analytical observational with a survey method and laboratory examination with a cross sectional approach. The sample for this research was 32 food samples from each rice stall produced. The results of bivariate analysis showed that the chi-square test (CI: 95%) had a significant relationship between food processing practices (p=0.037; PR=11.429) and sanitation hygiene (p=0.024; PR=14.000).